Suburbanization Economic and Management Challenges During the Covid-19 Pandemic - Lukasz KONOPIELKO (Communications of International Proceedings, 2021)
This paper presents preliminary conclusions resulting from a survey conducted in Poland at the end of 2020 on a representative research sample of 1500 respondents using the computer-assisted web interview method. The aim of survey was to outline the potential economic and non-economic motivations for changes in the place of residence and to examine the opinions on the phenomenon of suburbanization, and the impact of the pandemic situation on the issues connected with suburbanization processes. Implications of Covid-19 epidemic on public transportation, housing management and preferences as well as on service sector are investigated. Preliminary results of survey shows that the COVID-19 pandemic does not seem to be a factor radically influencing the housing preferences in Poland, while long-term stay at home has resulted rather in an appreciation of the current place of residence. Significant challenges have arisen for the local communities and in the sphere of housing and transport, both in urban and rural areas, as well as in areas subject to intense suburbanization processes. The demand for traditional transport services has decreased and it has been partially replaced by the demand for services related to the physical delivery of goods to the place of residence. The greater role of locality gives room for the development of services at the micro level, addressed to a relatively small group of consumers.
Keywords: Suburbanization; Covid-19; Housing; Public Transport.